Economic Gender Gap in Algeria - Namane, Chahrazad N.; Saqfalhait, Nahil Ismail (International Journal of Economics and Financial Issues, 2020)
This study aims to explore the gender gap in Algeria which consists of four dimensions: economic, educational, political, and health care through a comparative study, using a descriptive-analytical methodology. The data in this paper are extracted from global gender gap reports during the period between 2006 and 2018, in which 13 years of (GGG) reports show that Algeria is more successful in bridging the gender gap in education and health, whereas the political and economic gaps between women and men are far from being bridged. Women's economic participation and opportunity is a matter that Algeria had failed to address competently, rendering women's participation in Algerian economy and job market weak. This paper provides descriptive analysis to the gender gap development in the area of economic participation and opportunity, and gives some insights on the gender gap Sub-indexes for economical participation. Such a Gap can be attributed to a number of social and economic factors which are addressed in this paper, followed by some suggested recommendations on how to enhance the role of women in Algeria's economy. Keywords: gender gap, gender economic participation and opportunity gap, Algeria. JEL Classifications: J16, J71, O15 DOI: https://doi.org/10.32479/ijefi.10129